New life for old ideas : Chinese philosophy in the contemporary world : a festschrift in honour of Donald J. Munro - An, Yanming; Bruya, Brian, 1966-; Munro, Donald J. (The Chinese University Press, 2019)
Over five decades, Donald J. Munro has been one of the most important voices in sinological philosophy. Among other accomplishments, his seminal book The Concept of Man in Early China influenced a generation of scholars. His rapprochement with contemporary cognitive and evolutionary science helped bolster the insights of Chinese philosophers, and set the standard for similar explorations today. In this festschrift volume, students of Munro and scholars influenced by him celebrate Munro's body of work in essays that extend his legacy, exploring their topics as varied as the ethics of Zhuangzi's autotelicity, the teleology of nature in Zhu Xi, and family love in Confucianism and Christianity. Essays also reflect on Munro's mentorship and his direct intellectual influence. Through their breadth, analytical excellence, and philosophical insight, the essays in this volume exemplify the spirit of intellectual inquiry that marked Donald Munro's career as scholar and teacher.